The Importance of Raising Public Awareness in the Use of Social Media to Avoid Hoax News (Case Study of Kampung Jatake RW 006 Cibungbulang, Bogor) - Tajudin, Ahmad (Jurnal Pengabdian Nusantara, 2023)
The rapid development of technology and supported by the rapid spread of information could become an attack on humans themselves. Because on the one hand technological developments can make it easier for people to get information quickly. However, on the other hand, it can be seen that the flow of information that is too open in the mass media can be tarnished by the rapid spread of fake news. Therefore, people are encouraged to be more aware of using social media so they don't easily consume hoax news. This study uses qualitative research methods.